Envelhecimento e auto-eficácia: dispositivos assistivos desenvolvidos e adaptados pelos idosos - Mussolini, Claudia Cristina (2007)
Assistive devices are used by elderly people to help them in their daily tasks, at work and in their integration with the community. Such devices contribute to the improvement of the elderly s functional capacity. During our field research, our attention was drawn to the fact that some of the elderly people devised and made their own assistive devices. In order to understand such behavior, our study employed a quantitative approach through semi-structured interviews with five elderly people, residents of the city of São Paulo, Brazil. Results showed that through a facilitating physical and social environment, defined types of self-efficacy expression were enabled (BANDURA, 1977;1991;1993), thus allowing those elderly people to efficiently devise, make and use albeit with some functional limitations the device that they needed. Furthermore, the assistive device built by the elderly serves as a continuous feedback for their self-esteem, since it bears the marks of their identity and life history traits. The presence of self-efficacy in the elderly s personality is an inner resource capable of minimizing the effects of functional incapacities, which may, in turn, affect their well-being and quality of life during their ageing process. Therefore, geriatric assistance programs should support and encourage the creative and productive potential of older individuals as a means to ensure their social integration and participation